2007
DOI: 10.1074/jbc.m702719200
|View full text |Cite
|
Sign up to set email alerts
|

SLC1 and SLC4 Encode Partially Redundant Acyl-Coenzyme A 1-Acylglycerol-3-phosphate O-Acyltransferases of Budding Yeast

Abstract: Phosphatidic acid is the intermediate, from which all glycerophospholipids are synthesized. In yeast, it is generated from lysophosphatidic acid, which is acylated by Slc1p, an sn-2-specific, acyl-coenzyme A-dependent 1-acylglycerol-3-phosphate O-acyltransferase. Deletion of SLC1 is not lethal and does not eliminate all microsomal 1-acylglycerol-3-phosphate O-acyltransferase activity, suggesting that an additional enzyme may exist. Here we show that SLC4 (Yor175c), a gene of hitherto unknown function, encodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
129
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(141 citation statements)
references
References 37 publications
3
129
0
Order By: Relevance
“…Recently, four different research groups independently reported the identification of a yeast orthologue of this family as a LPLAT with most similarity to mLPCAT4 (MBOAT2) (46)(47)(48)(49). Notably, the enzymatic properties of yeast MBOAT are different from those of mouse MBOAT.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, four different research groups independently reported the identification of a yeast orthologue of this family as a LPLAT with most similarity to mLPCAT4 (MBOAT2) (46)(47)(48)(49). Notably, the enzymatic properties of yeast MBOAT are different from those of mouse MBOAT.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear at present whether another lysoPI-specific acyltransferase with different acyl donor specificity exists or if lysophospholipid acyltransferase with no head group specificity catalyzes the transfer of these fatty acids into PI exists. Very recently, a novel lysophospholipid acyltransferase was identified from yeast that catalyzes the transfer of unsaturated fatty acids into major lysophospholipids such as lysoPE, lysoPC, lysoPS, lysoPI, and lysoPA (Benghezal et al, 2007;Jain et al, 2007;Riekhof et al, 2007;Tamaki et al, 2007). Because other MBOAT family genes were found in C. elegans, one or more of these gene products may express the remaining LPIAT activity in mboa-7 mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemically characterized members of the family encode enzymes that transfer organic acids, typically fatty acids, onto hydroxyl groups of membrane-embedded targets. As mentioned above, several groups very recently cloned a yeast gene named ALE1 (Riekhof et al, 2007), SLC4 (Benghezal et al, 2007), or LPT1 (Jain et al, 2007;Tamaki et al, 2007) that encodes an acyltransferase of the MBOAT family. Deletion of this gene in yeast results in strong reduction of the activities of various lysophospholipid acyltransferases such as LPEAT, LPCAT, LPSAT, LPIAT, and LPAAT, suggesting that this newly identified acyltransferase is involved in the metabolism of a variety of lysophospholipids in the cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, this is currently the most comprehensive description of the S. cerevisiae lipidome achieved with Ϸ125-fold better sensitivity and Ͼ3-fold increased lipidome coverage compared with previous approaches (14,16,17). To demonstrate its efficacy for functional genomics studies, we monitored in molecular detail how the full lipidome adapted to growth temperature and genomic deletion of 3-ketoacyl-CoA synthases.…”
mentioning
confidence: 99%